Spatial analysis and mapping of the effect of irrigation and nitrogen application on lateral shoot growing of garlic - De Oliveira, Job Teixeira; De Oliveira, Rubens Alves; Puiatti, Mario; Teodoro, Paulo; Montanari, Rafael [UNESP] (American Society for Horticultural Science, 2020)
The objective of this study was to evaluate whether the spatial variability of plant production components and the use of an irrigation and fertirrigation management system with controlled deficit affect the yield and incidence of garlic lateral shoot growing (LSG). An analysis of these data through statistical and geostatistical techniques made it possible to verify that the increase in yield is directly related to the height and diameter of the bulb and that the lateral shoot growing is directly related to the increase in yield. Lower water depths and lower nitrogen doses applied during clove differentiation imply a lower incidence ofLSG, whereas increased irrigation and fertigation with nitrogen results in lower bulb volumes.
Keywords: Allium sativum; Geostatistics; Precision agriculture; Pseudogrowing